A comparative analysis of RNA isolation methods optimized for high-throughput detection of viral pathogens in California’s regulatory and disease management program for citrus propagative materials - Dang, Tyler; Bodaghi, Sohrab; Osman, Fatima; Wang, Jinbo; Rucker, Tavia; Tan, Shih-Hua; Huang, Amy; Pagliaccia, Deborah; Comstock, Stacey; Lavagi-Craddock, Irene; Gadhave, Kiran R.; Quijia-Lamina, Paulina; et al. (Frontiers in Agronomy, 2022)
Citrus germplasm programs can benefit from high-throughput polymerase chain reaction (PCR)-based methods for the detection of graft-transmissible pathogens in propagative materials. These methods increase diagnostic capacity, and thus contribute to the prevention of disease spread from nurseries to citrus orchards. High quality nucleic acids, as determined by purity, concentration, and integrity, are a prerequisite for reliable PCR detection of citrus pathogens. Citrus tissues contain high levels of polyphenols and polysaccharides, which can affect nucleic acid quality and inhibit PCR reactions. Various commercially available RNA isolation methods are used for citrus and include: phenol-chloroform (TRIzol®, Thermo Fisher Scientific); silica columns (RNeasy® Plant Mini Kit, Qiagen); and magnetic beads-based methods (MagMAXTM-96 Viral RNA Isolation Kit, Thermo Fisher Scientific). To determine the quality of RNA and its impact on the detection of graft-transmissible citrus pathogens in reverse transcription (RT) PCR-based assays, we compared these three RNA isolation methods. We assessed RNA purity, concentration, and integrity from citrus inoculated with different viruses and viroids. All three RNA isolation methods produced high quality RNA, and its use in different RT-PCR assays resulted in the detection of all targeted citrus viruses and viroids with no false positive or negative results. TRIzol® yielded RNA with the highest concentration and integrity values but some samples required serial dilutions to remove PCR inhibitors and detect the targeted pathogens. The RNeasy® kit produced the second highest concentration and purity of RNA, and similar integrity to TRIzol®. MagMAXTM isolation also provided high quality RNA but most importantly produced RNA with consistent results clustered around a median value for concentration, purity, and integrity. Subsequently, MagMAXTM-96 was combined with the semi-automated MagMAXTM Express-96 Deep Well Magnetic Particle Processor, for high-throughput sample processing. MagMAXTM-96 enabled the diagnostic laboratory of the Citrus Clonal Protection Program-National Clean Plant Network at the University of California, Riverside to process over 16,500 samples from citrus budwood source trees between 2010 and 2019. This high-throughput approach dramatically reduced the incidence of viroids in citrus nurseries and was key to the successful implementation of the mandatory Citrus Nursery Stock Pest Cleanliness Program in California.